PERANAN PROSES PERANCANGAN PRODUK PADA SENTRA INDUSTRI KERAJINAN SKALA KECIL MENENGAH DALAM ERA PERDAGANGAN BEBAS - Nurcahyanie, Yunia Dwie (Majalah Ekonomi, 2010)
The most of small-scale industry in Indonesia is at a center community. The activities of the entrepreneur of small scale industrial if seen from pattern link of its job environmentally its business own is difference of among one small entrepreneur with other. Based on the difference pattern of its link hence the small entrepreneur can be grouped into mains entrepreneur, entrepreneur of free entrepreneur and follower. The main entrepreneur is important position, which can determine to succeed in the reassignment of small industry at one particular of a center community. Therefore, to evaluate the readiness of small industry in face of free trade era hence attention and target of development shall be addressed to mains entrepreneur.